1985
DOI: 10.1111/j.1464-410x.1985.tb05860.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Morphometric Studies of the Human Obstructed, Trabeculated Urinary Bladder

Abstract: As part of an ongoing study on trabeculation of the human urinary bladder, morphological and morphometric techniques have been employed on biopsy samples of detrusor muscle removed from control and urodynamically obstructed patients. In control material the mean profile area, profile diameter and nucleated profile percentage of bladder smooth muscle cells were determined. The values of the same parameters were obtained for smooth muscle cells in samples from urodynamically obstructed and endoscopically trabecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
3

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(50 citation statements)
references
References 3 publications
4
43
0
3
Order By: Relevance
“…Gilpin et al (9) while studying the morphology and morphometry of detrusor muscle fibers from patients with obstruction, described structural changes of the vesical wall, represented by collagen deposit in muscular interstice, and by the increase in volume of muscle fibers, what is in accordance to our results.…”
Section: A B C Dsupporting
confidence: 82%
See 1 more Smart Citation
“…Gilpin et al (9) while studying the morphology and morphometry of detrusor muscle fibers from patients with obstruction, described structural changes of the vesical wall, represented by collagen deposit in muscular interstice, and by the increase in volume of muscle fibers, what is in accordance to our results.…”
Section: A B C Dsupporting
confidence: 82%
“…The vesical wall can accumulate connective tissue and evolve to a fibrotic process in consequence of a neurologic (myelomeningocele, spinal cord lesion) or obstructive (BPH) process. Such pathological conditions can result in low capacity, high pressure and low vesical compliance (9).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of detrusor smooth muscle secondary to the obstruction is often changed in a typical manner with the development of detrusor instability [1]. Structural adaptations might vary; in one study [2], the cross-sectional area of detrusor smooth muscle cells had increased suggesting hypertro phy, whereas an earlier study of the same group [3] showed subnormal cross-sectional cell areas. Connective tissue infiltration of the muscle bundles was found in both studies.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, ®brosis is present in the hypocompliant bladders of patients with myelomeningocele [10]. Similarly, there is connective tissue in®ltration into the muscle bundles of the obstructed unstable detrusor, which may show low compliance under conventional urodynamic conditions [11]. Indeed, it appears that any injury which results in a change in the connective tissue composition of any part of the bladder wall may result in a reduction in the compliance of that part.…”
Section: Discussionmentioning
confidence: 99%